2013
DOI: 10.3233/ip-130314
|View full text |Cite
|
Sign up to set email alerts
|

Local election blogs: Networking among the political elite

Abstract: This article explores the role of social media (essentially blogs) in the 2011 Norwegian local election campaigns. We commence by developing a framework for investigating political communication using the social media that conceptualises the horizontal and vertical conversation along two dimensions: participants and interaction. Next, we apply our framework in a case study of election blogs in twelve Norwegian municipalities using multiple data sources. In contrast to the democratic vision of social media, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For instance, Segaard and Nielsen (2013) explore the role of the election blogs in the 2011 Norwegian local election campaigns. They found that election blogs are primarily used by those who are politically active in other arenas as well and that most communication consists of one-way information dissemination.…”
Section: Literature Review: Identifying the Gapmentioning
confidence: 99%
“…For instance, Segaard and Nielsen (2013) explore the role of the election blogs in the 2011 Norwegian local election campaigns. They found that election blogs are primarily used by those who are politically active in other arenas as well and that most communication consists of one-way information dissemination.…”
Section: Literature Review: Identifying the Gapmentioning
confidence: 99%
“…Margolis and Resnick (2000:7) asserted that the use of the internet by political actors merely reflected and reinforced "politics as usual, conducted mostly by the same familiar candidates, interest groups, and news media." A diverse range of international studies, notably Gibson and Ward (2002), Gibson et al (2003) and Jankowski et al (2005) have supported this contention, demonstrating the use of the internet by political actors as a vertical or 'top-down', asymmetrical communications channel for information or party propaganda rather than a tool to develop two way horizontal political discussions with potential voters (Segaard and Nielsen, 2013). Similar results have been discovered in a number of UK electoral studies, including the 2005 UK general elections (Jackson, 2007), the 2008 London Mayoral election (Williamson et al, 2010), the 2004 European Parliament campaign (Ward, 2005) and the 2007 Scottish Parliament elections (Marcella, Baxter and Cheah, 2008).Whilst Saladow's (2012) notion that the traditional push approach which, although historically relevant, has been supplanted by a pull approach closely matches the current need for politicians, confronted by low levels of public trust, to entice voters into conversations (pull approach) with an aim to build long term relationships.…”
Section: )mentioning
confidence: 83%
“…Segaard and Nielsen's (2013) recent study of local election blogs conceptualised two models of digital communication in relation to social media: the horizontal and vertical conversation. The horizontal political conversation entails social networks characterised by symmetric conditions of participation (Rhodes and Marsh, 1992) whereby participants operate in non hierarchical structures and exchange opinions and knowledge freely (Segaard and Nielsen, 2013). Conversely vertical political conversations emphasises asymmetric flows of information from the political candidates/parties concerning policies, visions and programmes to voters who, during elections, then choose from these different products (Held, 2006).…”
Section: )mentioning
confidence: 99%
“…Additionally, most studies concerning the factors driving web campaigning do not account for individual attitudes and subjective assessments of the value of online platforms as campaign tools. Previous research findings have also confirmed a discrepancy between the intention to use web campaigning and the actual adoption (Marcinkowski and Metag, 2014;Segaard and Nielsen, 2013). By combining survey data with data regarding how candidates actually use social media, we expected to gain a deeper insight into the factors that drive the use of social media for election campaigning.…”
mentioning
confidence: 88%